HUMAN LANGUAGE AS NATURAL CODING: PHONOSEMANTIC PARALLELS BETWEEN TURKIC AND HEBREW (Лучшие интеллектуальные исследования, 2025)
Abstract: This article delves into the fascinating phonosemantic similarities between Turkic languages (like Uzbek and Kazan Tatar) and Hebrew. Words such as zamon (Uzbek) and zman (Hebrew) for “time,” ilohim (Uzbek) and elohim (Hebrew) for “God,” and olam (a shared term for “world” or “eternity”) reveal striking parallels in both sound and meaning. These examples point to deep cognitive and cultural universals in how languages evolve. Using the framework of Odam Tili (Human Language) theory, this study argues that these parallels are not random but reflect natural coding principles that shape language across diverse cultures.